Dissecting the ferroptosis-related prognostic biomarker and immune microenvironment of driver gene-negative lung cancer. Issue 16 (August 2022) - Zhou, Rui; Ma, Hao-chuan; Liu, Yi-hong; Chen, Xian; Chang, Xue-song; Chen, Ya-dong; Liu, Li-rong; Li, Yong; Zhu, Yan-juan; Zhang, Hai-bo
Despite significant advances in targeted and immune therapy for non-small cell lung cancer (NSCLC), effective therapies for wild-type epidermal growth factor receptor/anaplastic lymphoma kinase ( EGFR/ALK WT ) with low expression of programmed death ligand-1 (PD-L1) NSCLC remain elusive. Numerous studies have shown that ferroptosis plays an essential role in antitumor activity. To identify the molecular regulation patterns associated with ferroptosis, 351 EGFR/ALK WT NSCLC samples with low-level PD-L1 were extracted from The Cancer Genome Atlas (TCGA) and clustered using the k-means clustering technique. The two clusters associated with ferroptosis showed significantly different prognoses. In total, 169 differential expression genes (DEGs) were identified. Cluster differential analysis revealed that Cluster 1 had a significantly poorer overall survival (OS) and was associated with more negative immune regulation. In addition, TCGA samples were randomly assigned in a 7:3 ratio to a training group or testing group. A signature of eight genes associated with ferroptosis was established in the training cohort using DEGs and validated in the test cohort and three independent cohorts (GSE72049, GSE41271, and GSE50081). The 5-year area under the curve (AUC) was 0.713, which was significantly higher than that of other predictors, including TNM stage and age. Furthermore, the risk score was associated with immune function, immune infiltration, and immunotherapy response, with high-risk patients having a worse prognosis, an immune-suppressing phenotype, and a poor response to immune checkpoint inhibitors. This study aims to contribute to our understanding of the biological role of ferroptosis in EGFR/ALK WT NSCLC with low-level PD-L1, laying the groundwork for the development of novel therapeutic strategies.